Impact testing of navy bean pods - Adam, Nor Mariah; Burkhardt, T. H. (1986)
A pendulum system was developed for impacting navy bean pods. Impulse, maximum impact force and energy absorbed to shatter pods were measured. Impulse is the most suitable parameter to characterize impact resistance because it is independent of variety, time of harvest and pendulum release angle.